(untitled) (Communications in Computational Physics, 2020)
Due to α radioactive decay Pu is vulnerable to aging. The behavior of He in Pu is the foundation for understanding Pu self-radiation damage aging. Molecular dynamics technique is performed to investigate the behavior of defects, the interaction between He and defects, the processes of initial nucleation and growth of He bubble and the dependence of He bubble on the macroscopical properties of Pu. Modified embedded atom method, Morse pair potential and the Lennard-Jones pair potential are used for describing the interactions of Pu-Pu, Pu-He and He-He, respectively. The main calculated results show that He atoms can combine with vacancies to form He-vacancy cluster (i.e., the precursor of He bubble) during the process of self-radiation as a result of high binding energy of an interstitial He atom to vacancy; He bubble's growth can be dominated by the mechanism of punching out of dislocation loop; the swelling induced by He bubble is very small; grain boundaries give rise to an energetically more favorable zone for the interstitial He atom and self-interstitial atom accumulation than for vacancy accumulation; the process of He release can be identified as the formation of release channel induced by the cracking of He bubble and surface structure.